Groundwater management in the East of the European Union transboundary strategies for sustainable use and protection of resources - Nałęcz, Tomasz; SpringerLink (Online service). (Dordrecht Springer, 2011)
This volume is the result of work carried out under the NATO SPS Study Pilot Project "Sustainable Use and Protection of Groundwater Resources - Transboundary Water Management." It contains basic information on hydrogeological conditions, groundwater management and monitoring in areas of the Belarus, Lithuanian, Polish and Ukrainian borders, simultaneously borders of the European Union with its eastern partners. In view of the importance of the rational utilization of groundwater reserves, which is essential for our future existence, the book presents recommendations for a united methodology of an integrated groundwater monitoring system in this transnational area. The contributions also cover environmental and surface water issues that have direct effects on groundwater resources. The financial dimension of resource mobilization for environmental projects in Eastern Europe also features as part of a complex project solution.
Introduction -- Sustainable Use And Protection Of Groundwater Resources -- Transboundary Water Management -- Belarus, Poland, Ukraine Project As A Step For Establishing Integrated Transboundary Groundwater Management East Of Eu -- Further Perspectives Of The Project Sustainable Use And Protection Of Groundwater Resources. Transboundary Water Management -- Belarus - Poland, Ukraine,- Hydrogeological And Legal Problems Of Transboundary Aquifers In Poland; State Geological Survey Of Ukraine -- Groundwater Monitoring System In Belarus -- Groundwater Monitoring System In Lithuania -- Recommendations For Transboundary Groundwater Monitoring Organization Belarus, Lithuania, Poland And Ukraine Border -- Hydrogeological Problems Of Lviv Part Of Carpathian Region -- The Groundwater Of South-Eastern Poland And Problems Of Its Protection -- Groundwater Monitoring In The Border Area Of Poland With Lithuania -- Preliminary Assumptions For Transboundary Monitoring (On The Polish Side) -- Integrated Environmental Evaluation Western Buh River Basin (Ukraine And Poland) -- Creation Of The Polish-Belarusian-Ukrainian Water Policy In The Bug River Basin - The Project Carried Out Within Poland-Belarus-Ukraine Neighbourhood Programme Interreg Iiia/Tacis Cbc -- Contaminated Sites Investigation. The Environmental Case Study -- Comparison Of Ukrainian And Polish Groundwater Monitoring Methodologies In The Case Of Tests Made At Monitoring Points Located In The Border Area -- Financial Dimension Of Resource Mobilization For Environmental Projects In Eastern Europe; Lenodorska A -- List of Contributors.
Electronic reproduction.
Keywords: Groundwater -- Europe, Eastern -- Management -- Congresses; Groundwater -- Management -- Congresses; Water resources development -- Europe, Eastern -- Congresses; Electronic books